A dopaminergic mechanism of antipsychotic drug efficacy, failure, and failure reversal: the role of the dopamine transporter - Amato, Davide; Canneva, Fabio; Cumming, Paul; Maschauer, Simone; Groos, Dominik; Dahlmanns, Jana Katharina; Grömer, Teja W.; Chiofalo, Lisa; Dahlmanns, Marc; Zheng, Fang; Kornhuber, Johannes; Prante, Olaf; et al. (Molecular Psychiatry, 2018)
Antipsychotic drugs are effective interventions in schizophrenia. However, the efficacy of these agents often decreases over time, which leads to treatment failure and symptom recurrence. We report that antipsychotic efficacy in rat models declines in concert with extracellular striatal dopamine levels rather than insufficient dopamine D2 receptor occupancy. Antipsychotic efficacy was associated with a suppression of dopamine transporter activity, which was reversed during failure. Antipsychotic failure coincided with reduced dopamine neuron firing, which was not observed during antipsychotic efficacy. Synaptic field responses in dopamine target areas declined during antipsychotic efficacy and showed potentiation during failure. Antipsychotics blocked synaptic vesicle release during efficacy but enhanced this release during failure. We found that the pharmacological inhibition of the dopamine transporter rescued antipsychotic drug treatment outcomes, supporting the hypothesis that the dopamine transporter is a main target of antipsychotic drugs and predicting that dopamine transporter blockers may be an adjunct treatment to reverse antipsychotic treatment failure.
EVALuna2:35828

Blue-light treatment reduces spontaneous and evoked pain in a human experimental pain model. - Reuß, Anna Maria; Groos, Dominik; Scholl, Robert; Schröter, Marco; Maihöfner, Christian (Pain Reports, 2021)
Introduction: Chronic pain is a frequent severe disease and often associated with anxiety, depression, insomnia, disability, and reduced quality of life. This maladaptive condition is further characterized by sensory loss, hyperalgesia, and allodynia. Blue light has been hypothesized to modulate sensory neurons and thereby influence nociception. Objectives: Here, we compared the effects of blue light vs red light and thermal control on pain sensation in a human experimental pain model. Methods: Pain, hyperalgesia, and allodynia were induced in 30 healthy volunteers through high-density transcutaneous electrical stimulation. Subsequently, blue light, red light, or thermal control treatment was applied in a cross-over design. The nonvisual effects of the respective light treatments were examined using a well-established quantitative sensory testing protocol. Somatosensory parameters as well as pain intensity and quality were scored. Results: Blue light substantially reduced spontaneous pain as assessed by numeric rating scale pain scoring. Similarly, pain quality was significantly altered as assessed by the German counterpart of the McGill Pain Questionnaire. Furthermore, blue light showed antihyperalgesic, antiallodynic, and antihypesthesic effects in contrast to red light or thermal control treatment. Conclusion: Blue-light phototherapy ameliorates pain intensity and quality in a human experimental pain model and reveals antihyperalgesic, antiallodynic, and antihypesthesic effects. Therefore, blue-light phototherapy may be a novel approach to treat pain in multiple conditions.
EVALuna2:485662

Chronic antipsychotic treatment targets GIRK current suppression, loss of long-term synaptic depression and behavioural sensitization in a mouse model of amphetamine psychosis - Groos, Dominik; Zheng, Fang; Rauh, Manfred; Quinger, Benedikt; Kornhuber, Johannes; Müller, Christian P.; Alzheimer, Christian (Journal of Psychopharmacology, 2018)
BACKGROUND:: Antipsychotic drugs (APDs) are the mainstay of the pharmacological treatment of psychotic disorders like schizophrenia. While the clinical efficacy of APDs has long since been established, the neurobiological mechanisms underlying their therapeutic benefits are still not well understood. METHODS:: Here, we used an escalating amphetamine regimen to induce a psychosis-like state in mice. To achieve clinically relevant drug concentrations in amphetamine-pretreated mice, the typical APD haloperidol or the atypical APD olanzapine were chronically administered via subcutaneously implanted osmotic mini-pumps. RESULTS:: Demonstrating their therapeutic efficacy, both drugs dampened amphetamine-induced hyperlocomotion and restored normal behaviour in the light-induced activity test. Whole-cell recordings from dopaminergic neurons of the ventral tegmental area (VTA) in ex vivo brain slices revealed two pronounced aberrations associated with the psychosis-like state: Strongly enhanced spontaneous firing and a substantial loss of G protein-gated inwardly rectifying potassium (GIRK) current upon activation of GABAB receptors with baclofen. Chronic haloperidol and olanzapine restored normal firing and partially rescued the GIRK current response to baclofen. In ex vivo slices containing the nucleus accumbens, which receives a dopaminergic projection from the VTA, abrogation of long-term synaptic depression (LTD) and enhanced excitatory drive onto medium spiny neurons were identified as synaptic consequences of amphetamine-induced psychosis. Again, both alterations proved amenable to chronic APD treatment. CONCLUSION:: Our data provide evidence for aberrant neuronal function and plasticity in the mesolimbic dopamine system during an induced psychotic state and identify these alterations as targets of chronic APD treatment.
EVALuna2:35829

MCT4 Promotes Tumor Malignancy in F98 Glioma Cells - Reuß, Anna Maria; Groos, Dominik; Ghoochani, Ali; Buchfelder, Michael; Savaskan, Nicolai (Journal of Oncology, 2021)
Monocarboxylate transporter 4 (MCT4, SLC16A3) is elevated under hypoxic conditions in many malignant tumors including gliomas. Moreover, MCT4 expression is associated with shorter overall survival. However, the functional consequences of MCT4 expression on the distinct hallmarks of cancer have not yet been explored at the cellular level. Here, we investigated the impact of MCT4 overexpression on proliferation, survival, cell death, migration, invasion, and angiogenesis in F98 glioma cells. Stable F98 glioma cell lines with MCT4 overexpression, normal expression, and knockdown were generated. Distinct hallmarks of cancer were examined using in silico analysis, various in vitro cell culture assays, and ex vivo organotypic rat brain slice culture model. Consistent with its function as lactate and proton exporter, MCT4 expression levels correlated inversely with extracellular pH and proportionally with extracellular lactate concentrations. Our results further indicate that MCT4 promotes proliferation and survival by altered cell cycle regulation and cell death mechanisms. Moreover, MCT4 overexpression enhances cell migration and invasiveness via reorganization of the actin cytoskeleton. Finally, MCT4 inhibition mitigates the induction of angiogenesis, suggesting that MCT4 also plays a crucial role in tumor-related angiogenesis. In summary, our data highlight MCT4/SLC16A3 as a key gene for distinct hallmarks of tumor malignancy in glioma cells.
CRIS-Team Scopus Importer:2021-05-14

The acidic brain—glycolytic switch in the microenvironment of malignant glioma - Reuß, Anna Maria; Groos, Dominik; Buchfelder, Michael; Savaskan, Nicolai (International Journal of Molecular Sciences, 2021)
Malignant glioma represents a fatal disease with a poor prognosis and development of resistance mechanisms against conventional therapeutic approaches. The distinct tumor zones of this heterogeneous neoplasm develop their own microenvironment, in which subpopulations of cancer cells communicate. Adaptation to hypoxia in the center of the expanding tumor mass leads to the glycolytic and angiogenic switch, accompanied by upregulation of different glycolytic enzymes, transporters, and other metabolites. These processes render the tumor microenvironment more acidic, remodel the extracellular matrix, and create energy gradients for the metabolic communication between different cancer cells in distinct tumor zones. Escape mechanisms from hypoxia-induced cell death and energy deprivation are the result. The functional consequences are more aggressive and malignant behavior with enhanced proliferation and survival, migration and invasiveness, and the induction of angiogenesis. In this review, we go from the biochemical principles of aerobic and anaerobic glycolysis over the glycolytic switch, regulated by the key transcription factor hypoxia-inducible factor (HIF)-1α, to other important metabolic players like the monocarboxylate transporters (MCTs)1 and 4. We discuss the metabolic symbiosis model via lactate shuttling in the acidic tumor microenvironment and highlight the functional consequences of the glycolytic switch on glioma malignancy. Furthermore, we illustrate regulation by micro ribonucleic acids (miRNAs) and the connection between isocitrate dehydrogenase (IDH) mutation status and glycolytic metabolism. Finally, we give an outlook about the diagnostic and therapeutic implications of the glycolytic switch and the relation to tumor immunity in malignant glioma.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Acidic; Angiogenesis; Carbonic anhydrase (CA)IX; Glioma; Glycolytic; HIF; Lactate; MCT1; MCT4; Tumor microenvironment